Modification of Da’wah Through the Art Performance of Ki Dalang Ulin Nuha - Nisa, Nur Khoerun; Qalban, Anas Azhimi; Saputro, Dedy Riyadin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
This study aims to understand the messages, methods, and strategies carried out by puppeteers in changing the traditional da'wah format into an interesting and memorable art performance. Descriptive qualitative research was used to collect data, using observation, interviews, and content analysis of art performances performed by Ki Dalang Ulin Nuha. The research findings show the use of various strategies by Ki Dalang Ulin Nuha to deliver da'wah messages to the audience in his art performances, incorporating contemporary innovations such as the use of media & technology, music, sholawat, and interactive dialog with the audience. In addition, Ki Dalang Ulin Nuha also uses straightforward language and relates strict messages to everyday life. The modification of da'wah through Ki Dalang Ulin Nuha's art performances intends to reach and impact various levels of society. Ki Dalang Ulin Nuha's art performances attract audiences of all ages, including children, teenagers, and adults. The implication of this research is that the modification of da'wah through art performances can be an effective strategy in spreading religious messages to the wider community and can be used as a rol model in preaching that is not monotonous. Da'wah grows through larger art performances and inspires puppeteers and other artists to spread religious messages effectively, positively and attractively.